Sustainable Design and Manufacturing 2016 - Setchi, Rossi; Howlett, Robert J.; Liu, Ying.; Theobald, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volumes consists of 59 peer-reviewed papers, presented at the International Conference on Sustainable Design and Manufacturing (SDM-16) held in Chania, Crete Greece in April 2016. Leading-edge research into sustainable design and manufacturing aims to enable the manufacturing industry to grow by adopting more advanced technologies, and at the same time improve its sustainability by reducing its environmental impact. SDM-16 covers a wide range of topics from sustainable product design and service innovation, sustainable process and technology for the manufacturing of sustainable products, sustainable manufacturing systems and enterprises, decision support for sustainability, and the study of societal impact of sustainability including research for circulareconomy. Application areas are wide and varied. The book will provide an excellent overview of the latest research and development in the area of Sustainable Design and Manufacturing.
General Track 1: Sustainable Design, Innovation & Services -- General Track 2: Sustainable Manufacturing Processes & Technologies -- General Track 3: Sustainable Manufacturing Systems & Enterprises -- General Track 4: Decision Support and Sustainability -- Invited Session 1: Design for Additive Manufacture -- 6. Invited Session 2: Sustainability and Resilience in Agri-food Supply Chains -- 7. Invited Session 3: Eco-Design through Systematic Innovation -- Invited Session 4: Redistributed Manufacturing for Resilience and Sustainability -- 9. Invited Session 5: UK-China Forum on Innovation for Green Manufacturing.
Keywords: Computational intelligence; Artificial intelligence; Manufactures; Sustainability; Computational Intelligence; Artificial Intelligence; Machines, Tools, Processes; Sustainability